Seroepidemiology and antimicrobial susceptibility of Streptococcus pneumoniae isolated from patients with pneumococcal pneumonia - Hamzagić, Farah; Ranin, Jovana; Ranin, Lazar (Medicinski podmladak, 2021)
Seroepidemiology and antimicrobial susceptibility of Streptococcus pneumoniae isolated from patients with pneumococcal pneumonia Author: Farah Hamzagić, Jovana Ranin e-mail: hamzagicf98@gmail.com Mentor: Full Prof. dr Lazar Ranin, Institute of Microbiology and Immunology, Medical Faculty, University of Belgrade Introduction: Streptococcus pneumoniae is a major cause of community-acquired pneumonia (CAP). In Serbia, conjugate vaccines that contain 10 (PCV-10), or 13 (PCV-13) pneumococcal serotypes were licensed for immunization in 2018. Aim: The aim of this study was to evaluate serotype distribution and antimicrobial susceptibility of S. pneumoniae isolated from patients with pneumococcal pneumonia. Material and Methods: Isolates of S. pneumoniae were recovered from patients with CAP addmitted to 18 hospitals throughout Serbia from 2012-2020. Confirmation of the identification was performed using LytA gene detection by PCR. Serotyping and antimicrobial susceptibility testing was performed by Quellung reaction and disk diffusion/gradient test, respectively. Interpretation of the susceptibility testing was done according to the current European Committee on Antimicrobial Susceptibility Testing recommendations. Results: During the study period, a total of 100 isolates of S. pneumoniae were collected. Overall, 19 pneumococcal serotypes were identified. The predominant types observed, in order of decreasing frequency, were 3 (37%), 14 (16%), 6B (6%), 7F (5%), 9V (4%), and 4 (4%); further, 2% of the isolates were non-typeable. However, the most common serotype among children<2years old was 14 (27.3%). The vaccine coverage of strains isolated from children<5 years was higher with PCV-13 compared to PCV-10 (86.7% vs. 46.7%, p=0.008). Additionally, the vaccine coverage of pneumococci isolated from patients>2years was higher with the PPV-23 than with PCV-13 (96.6% vs. 84.3%, p= 0.0230). Ten isolates (10%) were PPV-23/nonPCV-13, whereas four isolates (4%) were non-typable (17A, 23A, and 9A). Serotype 3 significantly increased from pre-vaccine to post-vaccine period (30.8% vs. 60.8%, p=0.0108). The overall antimicrobial resistance rates were as follows: penicillin-9%, ceftriaxone-2%, erythromycin-24%, clindamycin-16%, tetracycline-11%, and trimethoprim-sulfamethoxazole-21%. Conclusion: More than 70% of the isolated strains belonged to the serotypes 3, 14, 6B, 9B, and 4. The highest resistance rates of the tested pneumococci were found for macrolides and trimethoprim-sulfamethoxazole. Keywords: Streptococcus pneumoniae; serotypes; antimicrobial resistance; pneumonia